Interaction between walkability and fine particulate matter on risk of ischemic stroke: A prospective cohort study in China. (1st January 2022) - Yang, Zongming; Wu, Mengyin; Lu, Jieming; Gao, Kai; Yu, Zhebin; Li, Tiezheng; Liu, Wen; Shen, Peng; Lin, Hongbo; Shui, Liming; Tang, Mengling; Jin, Mingjuan; et al.
Abstract: Living in walkable neighborhoods has been reported to be associated with a lower risk of cardiovascular disease. Features of walkable neighborhoods, however, may be related to particulate matter with an aerodynamic diameter ≤2.5 μm (PM2.5 ), which could increase risk of cardiovascular disease. The interaction effect between walkability and PM2.5 on risk of ischemic stroke remains to be elucidated. In this study, we recruited a total of 27, 375 participants aged ≥40 years from Yinzhou District, Ningbo, Zhejiang Province, China to investigate the associations of walkability and PM2.5 with risk of ischemic stroke. We used amenity categories and decay functions to evaluate walkability and high-spatiotemporal-resolution land-use regression models to assess PM2.5 concentrations. We used Cox proportional hazards regression models to calculate hazard ratios (HRs) and 95% confidence intervals (CIs). During a median follow-up of 4.08 years, we identified a total of 637 incident cases of ischemic stroke in the entire cohort. Higher walkability was associated with a lower risk of ischemic stroke (quartile, Q4 vs. Q1 walkability: HR = 0.59, 95% CI: 0.47–0.75), whereas PM2.5 was positively associated with risk of ischemic stroke (Q4 vs. Q1 PM2.5 : HR = 1.70, 95% CI: 1.29–2.25). Furthermore, we observed a significant interaction between walkability and PM2.5 on risk of ischemic stroke. Walkability was inversely associated with risk of ischemic stroke at lower PM2.5 concentrations, but this association was attenuated with increasing PM2.5 concentrations. Although walkable neighborhoods appear to decrease the risk of ischemic stroke, benefits may be offset by adverse effects of PM2.5 exposure in the most polluted areas. These findings are meaningful for future neighborhood design, air pollution control, and stroke prevention. Graphical abstract: Image 1 Highlights: Linking walkability and PM2.5 with ischemic stroke using a prospective design. Walkability was inversely associated with risk of ischemic stroke. Exposure to PM2.5 was positively associated with risk of ischemic stroke. Exposure to PM2.5 attenuated the beneficial effects of walkability.